2014
DOI: 10.1007/s13300-014-0071-1
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Improves the Impaired Acute Insulin Response during a Meal Tolerance Test in Japanese Patients with Type 2 Diabetes Mellitus: A Small-Scale Real-World Study

Abstract: IntroductionSeveral studies have shown that dipeptidyl peptidase-4 (DPP-4) inhibitors improve insulin secretion during oral glucose tolerance tests. However, the effects of DPP-4 inhibitors on impaired acute insulin responses in the postprandial state in real-world settings are unknown. Therefore, we evaluated the effects of sitagliptin on the acute insulin responses in Japanese patients with type 2 diabetes mellitus (T2DM) using meal tolerance tests.MethodsTwenty-one patients with T2DM were given a test meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Therefore, the improvement in postprandial blood glucose shown in the present study may be more strongly associated with suppression of glucagon secretion than with enhancement of insulin secretion with sitagliptin treatment in the very short-term. This finding contrasts with the results of previous studies, which have shown that DPP-4 inhibitors, including sitagliptin, may improve acute insulin response in Japanese patients with type 2 diabetes by increasing early-phase insulin secretion [ 6 , 13 ]. The previous studies had a longer follow-up period (about 12 weeks), and therefore secondary effects, including glucose toxicity, could have contributed to the response.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the improvement in postprandial blood glucose shown in the present study may be more strongly associated with suppression of glucagon secretion than with enhancement of insulin secretion with sitagliptin treatment in the very short-term. This finding contrasts with the results of previous studies, which have shown that DPP-4 inhibitors, including sitagliptin, may improve acute insulin response in Japanese patients with type 2 diabetes by increasing early-phase insulin secretion [ 6 , 13 ]. The previous studies had a longer follow-up period (about 12 weeks), and therefore secondary effects, including glucose toxicity, could have contributed to the response.…”
Section: Discussioncontrasting
confidence: 99%
“…However, some other researches conducted in non-diabetic subjects or type 2 diabetic subjects with a small sample size failed to observe any significant differences in insulin sensitivity between DPP4 inhibitor treatment group and placebo group [29,30]. Consistent with these data, we also found that increased DPP4 activities were positively associated with insulin resistance assessed by HOMA-IR in type 2 diabetic subjects.…”
Section: Discussionsupporting
confidence: 89%
“…107,108 Treatment with either GLP-1 agonists or DPP-4 inhibitors, as monotherapy or in combination with other agents, can restore the first-phase insulin response. [109][110][111][112] In the Liraglutide and the Preservation of Pancreatic β-Cell Function in Early Type 2 Diabetes (LIBRA) trial, following elimination of glucotoxicity with four weeks of IIT, treatment with liraglutide for 48 weeks led to further improvement in baseline adjusted insulin secretion to OGTT in patients with T2D. 113 In animal studies, the protective effects of liraglutide on betacell function were more pronounced in the early stages of T2D than in the advanced stages.…”
Section: Sglt-2 Inhibitorsmentioning
confidence: 99%